811. A Randomized Controlled Trial of Prednisolone vs. Interleukin 17 A Inhibitor Secuinumab in the Management of Type 1 Lepra Reaction in Leprosy Patients. (26th November 2018) - Mitra, Debdeep
Abstract: Background: Leprosy is a chronic granulomatous infectious disease caused by Mycobacterium leprae. Type 1 lepra reactions (T1R) are delayed hypersensitivity (Type IV) reactions which if not treated promptly leads to disability affecting eyes, hands and feet. IL-17 A which is produced mainly by inflammatory T helper 17 cells is up regulated in patients of Lepra reaction. Conventionally oral corticosteroids steroids have been the main stay in the management of Type 1 lepra reactions. This novel biologic drug is a targeted therapy which blocks the offending interleukin molecule without any serious adverse effects. We report the results of this randomized control study wherein an immuno-modulator biologic molecule has been safely used to treat an inflammatory reaction in a chronic infectious disease. Outcomes were measured using recurrence rate, a clinical severity score, quality of life, and adverse events. Methods: Seventy-four patients with new T1R were randomized to receive Secukinumab (a human IgG1κ monoclonal antibody that binds to the protein interleukin (IL)-17A) or Prednisolone for 20 weeks. IL-17 A levels were correlated before and after the intervention. Results: Recovery rates in skin signs was similar in both groups (92% vs. 87%). Improvements in nerve function both, new and old, sensory (67% vs. 48%) and motor (73% vs. 76%) loss were higher (but not significantly so) in the patients on Secukinumab. Recurrences rates of lepra reaction (25%) were high in both groups, and recurrences occurred significantly earlier (8 weeks) in patients on Secukinumab, who needed 10% more additional prednisolone. Serious major and minor adverse events rates were much lesser with Secukinumab as compared with Prednisolone alone. Both groups had a significant improvement in their quality of life after the study, measured by the Short form survey SF-36. Conclusion: This is the first double-blind randomized control trial assessing Secukinumab, in the management of lepra reaction. It could be a safe alternative second-line drug for patients with leprosy reactions who are not improving with prednisolone or are experiencing adverse events related to prednisolone. IL-17A levels could be an important diagnostic marker to diagnose and prognosticate cases of Type 1 Lepra reaction, which if not treated in time can lead to irreversible nerve damage. Disclosures: All authors: No reported disclosures.